A Space-Borne Ka-Band Tile-Type Phased Array Transmitter Module Based on HTCC Technology - Hui Xu; Kaixue Ma; Shuantao Li; Gaojian Liu (Applied Sciences)
We propose a double-sided layout design method with high reliability for multi-beam phased array transmitter modules based on high-temperature co-fired ceramic technology. Efficient transmission of microwave signals and low-frequency signals is realized by using multi-layer wiring and an inter-layer transition. The proposed Ka-band transmitter module exhibits a gain of ≥26 dB, an output power of ≥21 dBm, and an overall efficiency of the component of ≥40%. The RMS accuracy of phase shift and attenuation is better than 3° and 0.5 dB, respectively. The proposed design method addresses the problems of high integration, lightness, and miniaturization in transmit/receive module design, and shows a good performance of heat dissipation performance and sealing capability. It can be easily expanded to large-scale phased arrays.